Tramadol Iontophoresis Added to Treatment of Knee Osteoarthritis - Ayşe Dicle Turhanoğlu; Hayal Güler; Deniz İnanoğlu and Kerem İnanoğlu and Selim Turhanoğlu (Archives of Rheumatology, 2010)
Objective: The objective of the present study was to investigate whether tramadol iontophoresis added to therapy is superior to the therapy methods alone (transcutaneous electrical nerve stimulation (TENS), hot pack, ultrasound, and exercise therapy) in patients with knee OA. Materials and Methods: A total of 72 patients who admitted to the outpatient clinic of Physical Medicine and Rehabilitation were included in this study. The diagnosis was based on the American College of Rheumatology (ACR) criteria for knee OA. The patients were randomly separated into two groups. Group 1 received physical therapy and Group 2 received tramadol iontophoresis in addition to the therapy for a period of two weeks. Patients were evaluated according to pain and functional capacity assessed using visual analogue scale (VAS) and Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) before therapy and following the 10th session, and at 1 and 3 months. Results: The mean age and duration of the knee pain were 58.53±8.38, 5.00±2.66 years in the control group and 58.15±7.70, 4.71±2.70 years in the tramadol iontophoresis group. There were no significant differences between groups in the mean age and duration of the knee pain, body mass index (BMI), VAS and WOMAC scores before therapy. Following the 10th session, and after 1 and 3 months, VAS and WOMAC scores were significantly decreased in both groups when compared with the baseline values (p<0.001). VAS scores were significantly lower in the tramadol iontophoresis group compared to controls following the 10th session (p<0.001). However, no significant difference was found between WOMAC scores of the tramadol iontophoresis and control groups (p>0.05). Conclusion: We conclude that tramadol iontophoresis added to physical therapy may be useful for relieving pain of knee OA during the treatment period. (Turk J Rheumatol 2010; 25: 174-8)